Clinical presentation and treatment of cardiac myxoma in 153 patients. Issue 37 (September 2018) - Karabinis, Andreas; Samanidis, George; Khoury, Mazen; Stavridis, George; Perreas, Konstantinos
Abstract : Abstract: Cardiac myxoma (CM) is the most common benign cardiac tumor. We retrospectively reviewed our single center experience in 153 patients with CM over a period 25 years. From November 1993 to May 2017, 153 patients were operated in our institution with diagnosis of a CM. In all patients preoperative, perioperative, and postoperative data were recorded including the long-term follow-up. All patients followed up in the outpatient's clinics and echocardiography at regular intervals. Mean age 59 ± 12 years old. There were 104 women and 49 men. Preoperative clinical manifestations of the patients were hemodynamic consequences (47.7%), asymptomatic (46.4%), systemic embolism (4.5%), systemic manifestations-fever (0.7%), and hemoptysis (0.7%). The most common location of CM was in the left atrium in 82.4% patients. Mean tumors diameter was 4.5 ± 1.9 cm. In addition, we were observed that the age of the patients have differences between sex groups women versus men, 60.3 and 54.8 years old respectively ( P  = .02). On the other hand the tumor size have not differences between the sex groups ( P  = .56). Combine operations were performed in 24 (15.7%) patients. New cerebrovascular accident was observed in 2 patients post-op. Mean in-hospital stay was 8.02 ± 2.8 days. In-hospital mortality was 1 patient (0.7%) (from sepsis). During median follow-up 3.7 ± 4.3 years CM recurrence was identified in 5 (3.3%) patients. Surgical resection of CMs contributes in an excellent prognosis and associated with low complications and recurrences rate. Regular long-term follow-up is recommended in all patients with CM.